FACTOR ANALYSIS OF METABOLIC SYNDROME ON OFFSHORE FIELD WORKERS AT COMPANY X IN 2021 - Modjo, Robiana; Sulistyono, Eddy (Universitas Udayana, 2024)
Metabolic syndrome according to the American Heart Association (AHA) 2021 is a collection of 5 risk factors that can trigger heart attacks, diabetes, stroke and other cardiovascular diseases. The 5 risk factors are (1) increased triglyceride levels, (2) greater abdominal circumference, (3) increased blood sugar (4) decreased high density lipoprotein (HDL) levels, and (5) increased blood pressure. Based on the results of the 2021 Medical Check Up (MCU), all workers at PT X found that the prevalence of metabolic syndrome had increased to 22.4% compared to the previous year (16.2%). The purpose of this study was to describe the metabolic syndrome in offshore field workers at PT X in 2021 using the cross sectional method. From the research results it is known that the variables of family history, work shift, length of work, physical activity, sedentary behavior, sleep duration and smoking are not associated with the incidence of metabolic syndrome (p-value > 0.05). Age and BMI variables were associated with the incidence of metabolic syndrome (p-value <0.05).There was no difference between the eating patterns of respondents who had a history of metabolic syndrome and the eating patterns of respondents who did not have a history of metabolic syndrome. Therefore, it is necessary to promote the worker heath program to increase awareness of workers about health. Keywords: Metabolic Syndrome, Offshore Field Workers, Age, BMI